RECOMMENDATIONS FOR POSYANDU UTILIZATION IMPROVEMENT AMONG MOTHERS OF UNDER-FIVE CHILDREN BASED ON TOTAL CUSTOMER SACRIFICES ANALYSIS - Mukaromah, Nurul Hidayatul; Wulandari, Ratna Dwi (Universitas Airlangga, 2015)
ABSTRACT The coverage of under-five children weighed is an indicator of community participation in Posyandu. During 2012 until 2014, Puskesmas Kenjeran had not reached the target of this indicator. The objective of this study is to arrange recommendations for Posyandu utilization improvement based on total customer sacrifice analysis. This was a quantitative analytical study with observational approach and cross sectional design. The sampling was calculated by using multistage random sampling method. The interviews through instrument were conducted to 112 respondents to obtain information on Posyandu utilization and respondents sacrifice required to utilize Posyandu. The results showed that respondents thought time was the greatest sacrifice among monetary, energy, and psychological sacrifices. Spearman correlation test on any sacrifice required showed significant correlation (p<0.05), except for monetary sacrifice.This study concluded that even total customer sacrifices was very small, but the huge expense of time spent still made respondents to be less likely to utilize Posyandu. Therefore, efforts are needed to reduce the magnitude of the sacrifice required by community utilizing Posyandu in Puskesmas Kenjeran area. Keywords: Posyandu utilization, total customer sacrifices, under-five children weighed